Report on in vitro propagation from the Bh16 collection of Urochloa humidicola from seed - Florián, David; Castiblanco, Valheria (Bioversity International and the International Center for Tropical Agriculture, 2020)
The procedure of disinfection and in vitro sowing of a set of materials corresponding to the BH16 group of Urochloa humidicola was carried out at CIAT headquarters, with this it was possible to establish In Vitro plants without high percentages of contamination by fungi or bacteria, in addition to finding that the use of sulfuric acid for scarification procedures before sowing generates germination results similar to those that would be obtained in silica sand. This being a significant and pioneering advance in the standardization of In Vitro propagation methods for U. humidicola.